Implication of the Pro12Ala polymorphism of the PPAR-gamma 2 gene in type 2 diabetes and obesity in the French population - Charles Marie-Aline; Clément Karine; Charpentier Guillaume; Lobbens Stéphane; Meyre David; Ghoussaini Maya; Tauber Maïté; Weill Jacques; Froguel Philippe (BMC, 2005)
Abstract Background The Pro12Ala Single Nucleotide Polymorphism (SNP) of the Peroxisome Proliferator-Activated Receptor gamma 2 (PPAR-gamma 2) has been associated with insulin resistance and type 2 diabetes (T2D) and also inconsistently with obesity. The aim of this study was to evaluate the impact of this SNP with regards to T2D and childhood and adult obesity in the French Caucasian population. Methods We conducted three independent case/control studies encompassing 2126 cases and 1124 controls. Results We found a significant association between PPAR-gamma 2 Pro12Ala SNP and T2D (p = 0.04, OR = 1.37), which was stronger when the T2D cohort was stratified according to the obesity status (p = 0.03, OR = 1.81 in obese T2D subjects). In contrast, there was no association between the Pro12Ala SNP and childhood and adulthood obesity. In normal glucose tolerant obese adults (but not in lean subjects), the Pro12 allele was associated with a significant increase in fasting insulin levels (p = 0.01), and in insulin resistance estimated by the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) (p = 0.003), after adjustment for age, gender and BMI. We didn't detect evidence for an interaction effect between the Pro12Ala SNP and the obesity status with respect to the HOMA-IR index in normal glucose tolerant children, but we found a borderline interaction (p = 0.06) in normal glucose tolerant adults. Conclusion Our results showed that the Pro12Ala polymorphism is not associated with childhood or adult obesity in the French Caucasian population. In contrast, we confirm a contribution of the PPAR-gamma 2 Pro12 allele in the genetic risk forT2D, especially in obese subjects, where this allele worsens insulin resistanceand increases fasting insulin levels.